Pelatihan dan Pendampingan Pengelolaan Content Websitedi Akademi Gizi Karya Husada Kediri - Achmad Zakki Falani; Putu Artaya; Made Kamisutara; Latipah (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2025)
In today's digital era, a website is one of the essential tools an institution must have. It serves as a platform for publication, interaction, and communication with various stakeholders. A website is not only essential for online branding but also serves as an effective medium for interacting with various stakeholders, such as prospective new students, accreditation assessors, and so on. With the primary role of a website as the face of an online institution, it is crucial to understand proper website content management. Akademi Gizi Karya Husada which is located at Jl. Soekarno Hatta No. 07, Pare, Kediri, has a website with minimal content and relatively low frequency of data updates. Most of the website operators involved do not fully understand the use and management of a website because it is not in line with their area of expertise. With community service activities through training and mentoring for website content management at the Akademi Gizi Karya Husada Kediri, it is expected that the website operators involved can carry out their duties optimally, properly, and correctly, and the frequency of website content updates will increase.